2007
DOI: 10.1590/s1415-47572007000400020
|View full text |Cite
|
Sign up to set email alerts
|

Development of two sequence-specific PCR markers linked to the le gene that reduces pod shattering in narrow-leafed Lupin (Lupinus angustifolius L.)

Abstract: Wild types of narrow-leaf lupin (Lupinus angustifolius L.) have seed pods that shatter upon maturity, leading to the loss of their seeds before or during the harvest process. Two recessive genes have been incorporated into domesticated cultivars of this species to maximize harvest-ability of the produce. One of these genes is called lentus (le). Two microsatellite -anchored fragment length polymorphism (MFLP) candidate markers were identified as closely linked to the le gene in a recombinant inbred line (RIL) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 14 publications
0
23
0
Order By: Relevance
“…This modification results in a reduction of torsional forces upon drying and causes reduced pod shatter (Gladstones 1967). Three simple PCR-based molecular markers closely linked to lentus gene have been developed for narrow-leafed lupin (Boersma et al 2007c;Li et al 2012b). Two of them are dominant markers (LeM1 and LeM2), unable to discriminate between homozygous and heterozygous genotypes (Boersma et al 2007c).…”
Section: Pod Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…This modification results in a reduction of torsional forces upon drying and causes reduced pod shatter (Gladstones 1967). Three simple PCR-based molecular markers closely linked to lentus gene have been developed for narrow-leafed lupin (Boersma et al 2007c;Li et al 2012b). Two of them are dominant markers (LeM1 and LeM2), unable to discriminate between homozygous and heterozygous genotypes (Boersma et al 2007c).…”
Section: Pod Characteristicsmentioning
confidence: 99%
“…Three simple PCR-based molecular markers closely linked to lentus gene have been developed for narrow-leafed lupin (Boersma et al 2007c;Li et al 2012b). Two of them are dominant markers (LeM1 and LeM2), unable to discriminate between homozygous and heterozygous genotypes (Boersma et al 2007c). Recently, Li et al (2012b) reported the development of a new codominant marker (LeLi) flanking the lentus gene.…”
Section: Pod Characteristicsmentioning
confidence: 99%
“…Examples are mollis, which confers soft seediness (marker MoLi) [5]; tardus and le , which reduce pod shattering (markers TaLi, LeM1, and LeM2) [6,7]; and Ku , which removes the vernalization requirement (marker KuHM1) [8]. Furthermore, the MFLP method was used to develop sets of markers tagging hypothetical genes involved in lupin resistance to pathogenic fungi, including Lanr1, conferring anthracnose resistance (markers AntjM1 and AntjM2) [9-11]; Phr1 and Phr2 , carrying resistance to Phomopsis stem blight, a lupin disease caused by the necrotrophic fungus Diaporthe toxica (markers Ph258M1, Ph258M2, PhtjM1, and PhtjM2) [12,13]; Hua’an Yang, unpublished; and a pair of markers, RustM1 and RustM2, linked to rust-resistance loci [14].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, two PCR‐based markers for detecting the presence or absence of lentus gene were developed for narrow‐leafed lupin (Boersma et al. 2007).…”
mentioning
confidence: 99%
“…Plant materials: An F 8 recombinant inbred line (RIL) population was developed from a cross between a domesticated breeding line 83A:476 ( lentus/lentus ) and a wild‐type P27255 ( Lentus/Lentus ) of L. angustifolius using a single‐seed‐descent method (Boersma et al. 2007).…”
mentioning
confidence: 99%